2023
DOI: 10.1108/itp-07-2022-0529
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of normative and hedonic motivations on continuous knowledge contribution in virtual community: the moderating effect of past contribution experience

Abstract: PurposeThis paper aims to explore the effects of normative and hedonic motivations on continuous knowledge contribution, and how past contribution experience moderates the effects of the motivations on continuous knowledge contribution.Design/methodology/approachBased on goal-framing theory, the present study proposes a comprehensive theoretical model by integrating normative and hedonic motivations, past contribution experience and continuous knowledge contribution. The data for virtual community members' act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…As the success of social Q&A communities largely depend on the overall knowledge base, it is essential for members to provide a variety of perspectives on various topics. Extant studies have suggested that the motivation driving continuous knowledge contribution by community members differs from that of initial contribution, which is primarily influenced by external factors such as friend recommendations (Dong et al. , 2023).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…As the success of social Q&A communities largely depend on the overall knowledge base, it is essential for members to provide a variety of perspectives on various topics. Extant studies have suggested that the motivation driving continuous knowledge contribution by community members differs from that of initial contribution, which is primarily influenced by external factors such as friend recommendations (Dong et al. , 2023).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Third, most existing studies use questionnaires to collect data (Zhao et al, 2012;Mustafa and Zhang, 2022;Zhang et al, 2021), which may has a bias in self-reporting and only explores the intention or willingness to continue to participate instead of actual behavior. Besides, scholars have noted that users' motivations change over time, leading to the change in their perceptions and behaviors (Dong et al, 2023;Tsai and Bagozzi, 2014). Although a few studies collect actual behavior data of users, they mostly rely on cross-sectional data, which only considers the impact of motivations at a fixed time point and does not adequately account for the potential effects of changing differences over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations